Determinan Tax avoidance dengan Good Corporate Governance sebagai Variabel Moderasi - Fitra Wansyah Zuhri; Iman Indrafana Kusumo Hasbullah (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to determine the profitability, leverage, and transfer pricing on tax avoidance with Good Corporate Governance as a moderating variable in mining companies listed on the Indonesia Stock Exchange from 2019 to 2023. The sampling method used is purposive sampling. The total number of observations in this study was 140 samples over five years, comprising 28 companies. The data analysis technique used in this study was moderation analysis using Moderated Regression Analysis (MRA) using SPSS 26 The results of this study indicate that profitability has a negative effect on tax avoidance, leverage and transfer pricing do not affect tax avoidance, and Good Corporate Governance is unable to moderate the influence of profitability and leverage on tax avoidance. Additionally, Good Corporate Governance is able to moderate and strengthen the influence of transfer pricing on tax avoidance.